Designing a Human Resource Management System for Performance Assessment using Behaviorally Anchored Rating Scales (BARS) for Operators at PT. Polyland Indoteknik Bandung - Erlin Ribka Tanoni; Bobby W. Saputra (Riviera Publishing, 2024)
Employee performance appraisal is a crucial aspect of enhancing organizational productivity and effectiveness. This research aims to develop a more robust performance appraisal system for factory operators at PT. Polyland Indoteknik Bandung employs the Behaviorally Anchored Rating Scales (BARS) method. Through an analysis of the existing appraisal system, this study found that the sole use of Key Performance Indicators (KPIs) is insufficient to measure complex behavioral aspects. Therefore, BARS is proposed as a more comprehensive method. The designed BARS system incorporates specific behavioral indicators relevant to the job of factory operators. Additionally, this research outlines an implementation strategy involving socialization, integration with existing systems, feedback provision, and periodic evaluation. The results indicate that BARS can improve the quality of performance appraisals and provide more constructive feedback to employees.